Ultrathin, Core–Shell Structured SiO2 Coated Mn2+‐Doped Perovskite Quantum Dots for Bright White Light‐Emitting Diodes - Tang, Xiaosheng; Chen, Weiwei; Liu, Zhengzheng; Du, Juan; Yao, Zhiqiang; Huang, Yi; Chen, Cheng; Yang, Zhaoqi; Shi, Tongchao; Hu, Wei; Zang, Zhigang; Chen, Yu; et al. (Small (Weinheim an der Bergstrasse, Germany), 2019)
All‐inorganic semiconductor perovskite quantum dots (QDs) with outstanding optoelectronic properties have already been extensively investigated and implemented in various applications. However, great challenges exist for the fabrication of nanodevices including toxicity, fast anion‐exchange reactions, and unsatisfactory stability. Here, the ultrathin, core–shell structured SiO2 coated Mn2+ doped CsPbX3 (X = Br, Cl) QDs are prepared via one facile reverse microemulsion method at room temperature. By incorporation of a multibranched capping ligand of trioctylphosphine oxide, it is found that the breakage of the CsPbMnX3 core QDs contributed from the hydrolysis of silane could be effectively blocked. The thickness of silica shell can be well‐controlled within 2 nm, which gives the CsPbMnX3@SiO2 QDs a high quantum yield of 50.5% and improves thermostability and water resistance. Moreover, the mixture of CsPbBr3 QDs with green emission and CsPbMnX3@SiO2 QDs with yellow emission presents no ion exchange effect and provides white light emission. As a result, a white light‐emitting diode (LED) is successfully prepared by the combination of a blue on‐chip LED device and the above perovskite mixture. The as‐prepared white LED displays a high luminous efficiency of 68.4 lm W−1 and a high color‐rendering index of Ra = 91, demonstrating their broad future applications in solid‐state lighting fields. Ultrathin, core–shell structured CsPbMnX3@SiO2 quantum dots (QDs) are synthesized by slowly hydrolyzing tetraethoxysilane at room temperature. SiO2 coating can increase stability (thermal, water) for the Mn2+ doped perovskite QDs and prevent anion exchange among them. A white light‐emitting diode fabricated with CsPbMnX3@SiO2 and CsPbBr3 QDs exhibits a color rendering index of 91 at 10 mA.